Tuning the electrochemical properties by anionic substitution of Li-rich antiperovskite (Li2Fe)S1−xSexO cathodes for Li-ion batteries. Issue 40 (6th October 2021) - Mohamed, M. A. A.; Gorbunov, Mikhail V.; Valldor, Martin; Hampel, Silke; Gräßler, Nico; Mikhailova, Daria
Abstract : A tunable redox potential and electrochemical performance are realized by anionic substitution of S by Se for the Li-rich antiperovskite (Li2 Fe)SO cathode. Abstract : The development of electrode materials with multielectron redox functionality is imperative for next-generation Li-ion batteries with a high gravimetric capacity. Within this context, a Li-rich (Li2 Fe)SO antiperovskite cathode is a promising candidate exhibiting such multielectron cationic and anionic redox features, resulting in a reversible extraction/insertion of about 1.2 Li + per formula unit. However, it suffers from poor structural and cycling stabilities which hinder its practical application. Herein, we systematically investigate the effect of anionic substitution of S with Se on the structural, thermal and electrochemical properties of the (Li2 Fe)SO cathode. With increasing the Se content, higher thermal stability and lower sensitivity to moist air were obtained. Multi-stage cationic and anionic redox processes characterized the electrochemical activity of all the prepared (Li2 Fe)S1− x Se x O solid solutions. The cationic redox process was shifted to higher potentials while the anionic redox process was shifted to lower potentials upon the increase of the Se content. Among the various synthesized compositions, (Li2 Fe)S0.7 Se0.3 O exhibited the best electrochemical performance with a high discharge capacity of ∼245 mA h g −1 and an outstanding cycling stability at 0.1C current rate as well as nearly 100% capacity recovery after rate capability tests of 50 cycles. To deeply characterize (Li2 Fe)S0.7 Se0.3 O, various ex situ and in situ techniques were applied. In contrast to (Li2 Fe)SO, the substituted (Li2 Fe)S0.7 Se0.3 O material remains crystalline without the evolution of secondary phases or superstructures after the first charge/discharge cycle highlighting its enhanced structural stability. Similar to (Li2 Fe)SO, both the cation (Fe) and anions (S/Se) from (Li2 Fe)S0.7 Se0.3 O participate in the redox process.